The Relationship of Education Financing Management to Effectiveness and Efficiency in the Learning Process - Dwi Adinda Putri; Bashori Bashori (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2022)
Introduction/Main Objectives: This study aims to analyze the relationship between education financing management and effectiveness and efficiency in the learning process. Background Problems: The issue of education financing must be an essential part of education development. Educational financing management planning in fulfilling educational facilities and infrastructure must bring about an effective and efficient nature. Novelty: This study of the literature study approach is a differentiator from the results of other people's research. Research Methods: This research was prepared using qualitative methods and a literature research approach to obtain information from various references relevant to the subject matter and the purpose of this research. Finding/Results: This study shows that financing planning is essential in realizing national education. Conclusion: One of the supporting factors is the planning of adequate facilities and infrastructure through an effective and efficient education financing plan. The process of planning and managing the financing of educational institutions is excellent and appropriate, and it will impact the provision of school facilities and infrastructure to the maximum. Finally, the process will also significantly affect the quality of education globally.